Induction of scratching behaviour in cats: efficacy of synthetic feline interdigital semiochemical. Issue 10 (October 2013) - Cozzi, Alessandro; Lecuelle, Céline Lafont; Monneret, Philippe; Articlaux, Florence; Bougrat, Laurent; Mengoli, Manuel; Pageat, Patrick
The aim of the study was to evaluate the effects of synthetic feline interdigital semiochemical (FIS) on the induction of scratching behaviour in cats during a standardised behavioural test. The trial was a randomised blinded study on a single group of subjects, following a crossover design. The scratching behaviour of 19 cats was evaluated during a standardised test in which cats were introduced to an area with one scratching post. Each cat acted as its own control (receiving, at random, FIS then placebo or vice versa). The test lasted for 5 mins, after which the cat was left alone in the test area. Duration, frequency of scratching and latency of first scratching behaviour were noted. Two independent observers analysed the videos. Thirty-eight tests were recorded with a different scratching post each time (two tests per cat). The scratching post with the semiochemical was more scratched in duration and frequency by the cats involved in the study (intention to treat analysis). The same conclusion was found using per-protocol analysis, which included only cats that scratched during the test. Regarding latency, no significant difference was found between treatment and placebo. The results seem of interest in explaining the role of a FIS in inducing scratching behaviour on a scratching post. The semiochemical approach can modify the choice of areas selected spontaneously by cats, and could be used either as a preventive measure for a cat arriving at home or to control or change an inappropriate scratching behaviour.